Fixed Point Theorems and Error Bounds in Partial Metric Spaces. (31st December 2013) - Mohsenalhosseini, S. A. M.
Abstract : This paper is introduced as a survey of result on some generalization of Banach's fixed point and their approximations to the fixed point and error bounds, and it contains some new fixed point theorems and applications on dualistic partial metric spaces.